The Impact of Analyst Following on Accounting Information Quality - Xuan Shujin (SHS Web of Conferences)
This article mainly discusses the impact of analyst tracking on accounting information quality based on the background of analyst tracking and accounting information quality. However, the specific path of the interaction between the two and the mechanism of their impact on the capital market have not been fully revealed in existing research. This study seeks to address these gaps by examining how analyst tracking impacts the quality of accounting information and exploring the regulatory and feedback effects of their interaction on the capital market.Specific problem analysis is conducted on the impact of analyst tracking on accounting information quality, and qualitative analysis is used to conduct literature review methods. Finally, it is concluded that analyst tracking has an impact on accounting information quality in terms of transparency and tracking willingness, complexity and information interpretation threshold. It regulates and feedbacks the capital market and proposes methods to strengthen supervision. By combining these literature with our research, our study demonstrates the importance of regulatory policies seeking a balance between enhancing accounting transparency and regulating analyst independence. Therefore, our research provides theoretical support for the formulation of future regulatory policies.